MANAGEMENT OF HUMAN CAPITAL DEVELOPMENT IN UZBEKISTAN - Akhunov Muhammadamin Abduvasitovich (Journals Park Publishing, 2022)
The article discusses human capital, which is a topical issue in the theory and practice of economics, and its role in the socio-economic development of our country. Suggestions for human capital employment management systems are outlined.
Keywords: human capital; capital; employment